Corpus-driven genre pedagogy of English for research publication purposes: Toward an ELF-referenced critical teaching framework - Lubis, Arif Husein (International Journal of Education, 2020)
Ever since the NNES and novice writers became actively engaged with international publications, the pedagogy of English for research publication purposes (ERPP) has received considerable attention from the EAP/ESP scholars using corpus-driven genre pedagogy. However, the quality of its implementation is still understudied. This study, therefore, critically reviews the qualitative milestone of corpus-driven genre pedagogy of ERPP. Nineteen (19) relevant research-based articles about corpus-driven genre pedagogy in the last 15 years from 2004 to 2019 were selected from Google Scholar and three top-tier journals in this realm: Journal of Second Language Writing, English for Specific Purposes, and Journal of English for Academic Purposes. Three stages were conducted, i.e. preparation, screening and validation, and content review. The findings encompassed: 1) the materials development process, 2) the learners’ engagement, and 3) the development of learners’ research writing competencies and clinical soft skills. The findings become the bases for proposing a framework of ELF-referenced critical corpus-driven genre pedagogy of ERPP.